Correction Method for Resuspended Road Dust Emission Factors according to Vehicle Speed Using a Mobile Monitoring Vehicle - Sang-Hee Woo; Hyoungjoon Jang; Seung-Bok Lee; Juyoung Jeong; Choonghwan Lee; Seokhwan Lee (Aerosol and Air Quality Research)
Abstract A mobile monitoring vehicle was used to measure road dust concentrations and determine resuspended road dust emission factors (EFs). By comparing the dust signal from the mobile monitoring vehicle and the EF calculated from a PM flux measurement using a flux tower, it was possible to convert the dust concentration detected by the mobile monitoring vehicle into resuspended road dust EF. On-road driving studies were conducted at various vehicle speeds on six different roads to determine the relationship between vehicle speed and resuspended road dust EF. The resuspended road dust EF exponentially increased with vehicle speed. A speed-related correction approach was established to reduce the variability in resuspended road dust EF caused by variations in vehicle speed. A mobile monitoring vehicle was used to determine the EFs of resuspended road dust from motorways and urban and rural roads in the Daejeon metropolitan of Korea. Local hot spots with high silt loading were identified by adjusting the EF according to vehicle speed. Additionally, three repeated measurements taken along the same route confirmed that EF deviation between measurements could be decreased by ≥ 50% after adjustment. In this study, we devised a vehicle speed-related correction method to obtain accurate and reliable EFs of resuspended road dust using a mobile monitoring vehicle, even based on a single on-road driving measurement.